Analysis of complete mitochondrial genome of Matuta planipes (Decapoda, Brachyura, Matutidae) from South Korea. Issue 1 (2nd January 2019) - Kim, Jung-Il; Dinh Do, Thinh; Karagozlu, Mustafa Zafer; Kim, Chang-Bae
Abstract: In the present study, a complete mitochondrial genome of the moon crab species, Matuta planipes was sequenced and analyzed. This is the second complete mitochondrial genome record for the species and the first record from South Korea. The genome structure and gene orientation are identical but the protein-coding gene sizes are slightly different in comparison with the previous record. Additionally, the phylogenetic relationship of M. planipes was investigated using protein-coding genes of the complete mitochondrial genome. The present study suggests that the closest species to M. planipes is Ashtoret lunaris and they belong to the family Matutidae. This study provides additional data for the family Matutidae phylogeny.